PENGARUH PEMBERIAN AIR KELAPA MUDA UNTUK MENINGKATKAN KADAR KALIUM DARAH PADA MENCIT - Christ Kartika Rahayuningsih (Jurnal Ilmu dan Teknologi Kesehatan, 2016)
Young coconut water (Cocos nucifera Linn) is a natural isotonic beverage which contains most of the potassium that can replace lost minerals in the body and has great potential to prevent dieses, so this study aims to determine the effect of coconut water (Cocos nucifera lin) to increase levels potassium blood in mice (Mus musculus). This study is experimental with design 'Postes Only Control Group Design' usingmultisensor to 24 mice of the same species is Mus musculus into 4 groups (6 mice pergroup) with the criteria of sex male mice, aged 2-3 months, weight about 20-40 g withnormal potassium levels from 4.30 to 5.60 mmol / L. Of the samples analyzed obtainedblood potassium levels in mice that is group A without drinking coconut water (control)of 4.65%, group B before taking 1 cc of coconut water amounted to 4.62% and afterdrinking increases to 7.53%, group C before drinking 0.5 cc coconut water amounted to4.87% and after taking into 6.27%, group D before drinking coconut water 0.1 cc of4.20% and after taking into 5.40%. Results of One Way Anova analysis we canconclude that there is the effect of coconut water (Cocos nucifera lin) to increase bloodpotassium levels in mice (Mus musculus).